Maternal Attitudes Regarding Stimulation: Main Predictors of Postnatal Development Factors in Children Aged 12-60 Months During Covid-19 Pandemic - Rusana, Rusana; Aprilianingsih, Nur; Subandi, Ahmad; Ekawati, Heni; Hasinuddin, M.; Ramawati, Dian; Ariani, Ida (Indonesian Journal of Global Health Research, 2024)
Child development can be influenced by postnatal factors such as stimulation mother, which plays an important role, in addition to factors nutritional status and chronic diseases in children. The existence of the COVID-19 pandemic risks increasing the child's pain rate. This study aims to determine the postnatal factors that influence and predominantly affect the development of children aged 12–60 months during the COVID-19 pandemic in the South Cilacap Region. The design used is survey-analytic, with a cross-sectional study. A large sample of 106 mothers and children aged 12–60 months with the cluster random sampling technique. Data was collected based on the results of interviews using a questionnaire via a Google Form link and and measuring child development using the SDIDTK application. Bivariate analysis used chi-square, while multivariate analysis used multiple logistic regression. The results showed that there is a significant influence of, maternal attitudes, knowledge about developmental stimulation and chronic diseases in children on the development of children aged 12–60 months during the COVID-19 pandemic in the South Cilacap Region (pv= 0,005; pv= 0,005; pv= 0,042). There is no influence of nutritional status factors on the development of children aged 12–60 months during the COVID-19 pandemic in the South Cilacap Region (pv= 0,385). The mother's attitude about developmental stimulation is the dominant factor that affects the development of children aged 12–60 months during the COVID-19 pandemic in the South Cilacap Region, Mothers who have a positive attitude towards development have a 69,249 times higher chance of having children with appropriate development compared children's chronic diseases and mothers' knowledge about stimulating children's development (pv= 0,005; α= 0,05; OR= 69,249). Mother's attitude about stimulation is important in child development. Education and knowledge can shape a mother's attitude so that more education is needed to achieve appropriate child development.